If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 3 = 2y + 12 Reorder the terms: 3 + 3y = 2y + 12 Reorder the terms: 3 + 3y = 12 + 2y Solving 3 + 3y = 12 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 3 + 3y + -2y = 12 + 2y + -2y Combine like terms: 3y + -2y = 1y 3 + 1y = 12 + 2y + -2y Combine like terms: 2y + -2y = 0 3 + 1y = 12 + 0 3 + 1y = 12 Add '-3' to each side of the equation. 3 + -3 + 1y = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 12 + -3 1y = 12 + -3 Combine like terms: 12 + -3 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| 6-2(x-2)=6(x+3) | | 260=x^3(2x^2+3x-8) | | -40-10y+18=-29y+44+8y | | 260=2x^5+3x^4-8x^3 | | 4x+9=7x+6 | | x^2=50 | | 9+5n=-11 | | 5x-10=5x-10 | | 2(x+2)=x+7 | | 8m-14=17 | | 15k+6=3k-3 | | x^4-10x^3=0 | | 3n+10=-2 | | 9x-7x-4x=-2 | | 11x+(-6x)=10 | | c^2=54-3c | | y-17=27 | | 4(4x-3)+7(x-5)= | | 4x-4x=3x+4 | | x^2+11xy-19y^2+2x+8y+22=0 | | 2-4=-3x+6 | | .75t+4=.75t-5 | | x^2-10x-6=2x+3 | | 2v-3=3 | | y=4x^2+8x-12 | | 4Y-16+8Y=4 | | x^2-10x+20=-5 | | hi=90348092384 | | 11x+8-5=10x-2 | | 6+x-10=-22 | | -22-3d=2d+d-3d | | 7x-14x-49=7 |